Development of Porous Refractory Calcium Hexaluminate (CA6) Ceramic Material from Limestone Waste - A. G. S. Costa; M. L. Silva; A. C. A. Prado; D. B. Silva; T. M. B. F. Oliveira; W. B. A. Bezerra (Materials Research)
Calcium hexaluminate (CA6) is a refractory material with good thermal properties and intrinsic difficulty in densification.This study explored the use of Cariri Stone residue, a calcium carbonate-rich limestone from Ceará, Brazil, as a precursor for producing refractory ceramics containing this phase. X-ray diffraction and preliminary tests were conducted to determine the optimal conditions for its incorporation into ceramic refractories. The results showed that a mixture of Cariri Stone residue and alumina, with a molar ratio of 0.5 moles of calcium oxide to 6 moles of aluminum oxide, achieved the best formation of CA6 at 1500°C. Specimens calcined at 1400°C exhibited the highest apparent porosity, indicating potential for thermal insulation applications. These findings highlight the feasibility of reusing Cariri Stone residue as a precursor for producing refractory ceramics containing the CA6 phase, offering a sustainable and promising alternative.